2001
DOI: 10.1042/bj3600557
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced production of a 40 kDa immunoreactive thyroglobulin fragment in human thyroid cells: the onset of thyroid autoimmunity?

Abstract: We recently reported that, during in vitro thyroid-hormone synthesis, H2O2 stress cleaved thyroglobulin (Tg) into C-terminal peptides. These peptides were found to contain the immunodominant region of Tg recognized by Tg autoantibodies from patients with an autoimmune thyroid disease. To test the hypothesis that Tg fragmentation is an early upstream initiating event involved in Tg autoimmune response and the consequence of oxidative injuries, we studied the effect of H2O2 stress on human thyroid cells. In cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Additionally, treatment of FRTL cells with genistein significantly increased the content of P40, an identified autoimmunogen that might be responsible for the onset of ATD. 3,5,11,12,33 The content of the intact Tg (P330) was increased in parallel with P40 by the same genistein and Novasoy treatments. Novasoy also increased, although to a lesser extent, the content of P330 and P40 Tg fragments that may be attributed to the action of the genistein contained.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, treatment of FRTL cells with genistein significantly increased the content of P40, an identified autoimmunogen that might be responsible for the onset of ATD. 3,5,11,12,33 The content of the intact Tg (P330) was increased in parallel with P40 by the same genistein and Novasoy treatments. Novasoy also increased, although to a lesser extent, the content of P330 and P40 Tg fragments that may be attributed to the action of the genistein contained.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies showed that the amount of cleaved Tg peptides increased in proportion to the iodoamino acid content of Tg molecules. 3,33 Moreover, higher thyroid hormone synthesis and iodination were associated with generation of excessive reactive oxygen species, resulting in the oxidative cleavage of Tg to produce P40 and expose its cryptic epitopes. 11,12 Increased production of reactive oxygen species also induces cell necrosis which in turn causes an inflammatory response that triggers thyrocytes to internalize P40 and present them to T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory lesions in the thyroid gland result in the destruction of follicular cells and fibrosis, leading to hypothyroidism [67]. NOX participation in the production of hydrogen peroxide for the purposes of thyroid hormone synthesis may be associated with the pathophysiology of autoimmune thyroid diseases, through interacting with thyroperoxidase and thyroglobulin (TG) and altering their activity, promoting immunogenicity [75,81]. Excessive iodine intake is regarded as an additional risk factor for the development of autoimmune thyroid disease due to enhancing ROS production and, at the same time, reducing internal antioxidant levels.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…66 The high level of H 2 O 2 also produces the antigenic antigen from oxidation damaged iodinated Tg. 68 Antioxidants blocked the generation of ROS and ICAM-1 expression. In a non-susceptible mouse, 100 μmol/L iodide did not generate H 2 O 2 .…”
Section: Ros-mediated Thyroid Diseasesmentioning
confidence: 99%